Battery Thermal Management System in ElectricVehicles using Phase Change Material (PCM) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
With the advancement in technology, the world is moving fast and for its fast growth, the automobile sector is also in the revolution period with the advancement in battery-driven vehicles. The Electric and Hybrid vehicles which run on the battery, face the main issue in thermal management. As there are so many electronic components inside the vehicle especially the battery, the heat dissipation is also more. Many of the researchers have proposed the Li-Ion cells as the most suitable for the battery packs in electric vehicles. And with many advantages of the Li-Ion cells, there is one major limitation of it as its heat dissipation rate. In order to get the best working performance of the battery electric vehicles, it’s equally important to keep its temperature in control. The various parameters which directly influence the temperature rise of the PCM are mass of PCM, the thermal conductivity of the Paraffin material, water flow rate etc.